Frequency of Contact Lens Complications Between Contact Lens Wearers Using Multipurpose Solutions Versus Hydrogen Peroxide in the United States and Canada. Issue 5 (May 2021) - Tichenor, Anna A.; Cofield, Stacey S.; Gann, Drew; Elder, Marian; Ng, Alison; Walsh, Karen; Jones, Lyndon W.; Nichols, Jason J.
Abstract : Objectives: To retrospectively compare frequency of contact lens (CL) complications in soft CL users of hydrogen peroxide (H2O2) and multipurpose solutions (MPS). Methods: This was a multicenter, retrospective chart review of CL records from each patient's three most recent eye examinations at academic and private practices. Patients must have used the same solution type for at least 3 years. Univariate analyses were conducted using t tests, and chi-square or Fisher's exact test for categorical measures. Results: There were 1, 137 patients included, with 670 (59%) using MPS and 467 (41%) H2O2. In total, 706 (62%) experienced at least one complication; 409 used MPS and 297 used H2O2. There was no difference in the proportion of patients experiencing at least one complication between MPS (61%) and H2O2 (64%) ( P =0.38). Multipurpose solutions users were more likely to report discomfort compared with H2O2 users ( P =0.04). Presumed microbial keratitis was experienced by 16 MPS and nine H2O2 users ( P =0.60). Conclusions: No significant differences were found in the frequency of CL complications between MPS and H2O2. H2O2 users were less likely to report discomfort and thus switching to a H2O2 system may be an alternative in CL users with discomfort.